The Influence of Teaching Effectiveness and Grading of Students’ Work on how Students Evaluate Their Lecturers - Chisango, Tadios; Kurevakwesu, Wilberforce; Mafa, Itai; Tapiwa, Simango; Mhizha, Samson (International Journal of African Higher Education, 2025)
This article presents an experimental test of the effects of teaching effectiveness and grading on evaluation of lecturers by students. Although lecturers’ grading of students’ work presents a key confounding variable in studies that investigate the influence of teaching effectiveness on lecturer evaluations by students, most existing studies use correlational studies. This makes it difficult to separate the effects. In the present study, teaching competence and lecturer’s grading of students’ work were manipulated orthogonally, in a between-participants design, with a sample of Zimbabwean students, to test their effects on the students’ endorsement of the lecturer , and also on potential lecturer evaluation. Hence, there were four experimental conditions: low-teaching competence-low grading, low teaching competence-low grading, high teaching competence-high grading and high teaching competence-high grading. The study tested the following specific hypotheses: (1) The low teaching competence-low grading condition would receive the lowest ratings on dependent measures; (2) The high teaching competence-high grading condition would receive the highest ratings. Results were largely in line with the hypotheses. These results show the benefits that accrue to instructors through giving students high grades. In particular, lecturers with low teaching competence can ‘buy’ better student ratings by assigning higher grades to students' work, while those with high teaching competence can enhance their ratings even more by giving high grades. Importantly, competent lecturers who grade their students lowly seem to be at the greatest disadvantage, in that they receive rather low ratings. The results indicate the flaws inherent in student evaluations of lecturers when their (lecturers’) levels of competence are also taken into consideration. The results are further discussed in regards with the necessity to refining related research, and more rigorous evaluation methods of lecturers’ performance in the classroom.